Corpo e máquina : estudo etnográfico em uma clínica de hemodiálise - Santos, Viviane Fernandes Conceição dos (2012)
This master s degree dissertation is an ethnographic study carried in the Clínica de Nefrologia de Sergipe with fifteen people that accomplish Renal Replacement Therapy type hemodialysis. It s presented an anthropological approach of the theme, focusing the experiences private and collective of those subjects in the clinic daily. Starting from the phenomenological perspective, the present subjective aspects in the established relationships during the treatment were discussed, as their expectations of the possibility of transplants, taking as backdrop the current donation and transplant framework in Sergipe State. Typical difficulties of this boundary condition that put them between body and machine, life and death were explored. The perspective of the corporeality has allowed the identification and understanding of hemodialysis experience dimensions in multiple senses. The world vision and the ethos of the people in treatment can contribute to divest hemodialysis of the sense of personal tragedy and incorporate it as a lifestyle.